Enhancing English Language Teaching and User Experience in Virtual Environments: A Systematic Review on Gamification and Personalised Learning - Myriam Tatiana Velarde Orozco; Bárbara Luisa De Benito Crosetti (Journal of Language and Education, 2025)
Introduction: Virtual learning environments (VLEs) have become central to English language teaching (ELT), although persistent disengagement suggests that design must go beyond content delivery. Gamification and personalised learning (PL) contribute to enhanced user experience (UX) and better learning outcomes, but evidence on their combined effects remains fragmented.